Daraiti Ahã : escrita alfabética entre os Enawene Nawe - Zorthêa, Katia Silene (2006)
The word daraiti passed to translate the alphabetic writing among the Enawene Nawe. The writing was inserted in daily of this people in 1995, and live with that and others forms tradicionals, specifics and singulars of language, valueds and transmiteds from then on imemorials times. This work claims make a historical system of this experience, showing that the work´s acsitions defines a process straightlyconnected to the people’s interests. The writing alphabetic’s accsition, in this case, don’t was used of the school institution to develop itself, the dynamic was defined by the Enawene Nawe, from their interests. Understand the multiples interpretations that tradition oral’s societies can make of writing, over try to produce an insert argument in discussion treating about teach red ans write’s methodologies.